The incidence and mortality rates due to stroke and myocardial infarction following implementing the package of essential non-communicable diseases; A historical cohort study - Sayed Ali Ayat; Shayeste Rostami; Reza Khadivi (Journal of Cardiovascular and Thoracic Research, 2022)
Introduction: The package of essential non-communicable diseases (PEN) has been implemented in 2016 in Iran. The present study aimed to evaluate the incidence rate of myocardial infarction (MI) and stroke, and the mortality rate due to these diseases, following the lunch of the PEN project. Methods: This is a historical cohort study that was performed in 2020. Data were gathered through the hospital information system in the exposed and the control counties hospitals in the Isfahan province. The data about over 30-year-old patients who were hospitalized as definite cases of MI and/or stroke were collected via census sampling. The incidence rates of MI, stroke, and mortality due to those diseases were compared in 2015 (one year before the launch of the PEN project) and 2019 (4 years after the project initiation). Results: Following the implementation of the PEN project, the incidence and mortality rates due to MI among the over 30-year-old population in the exposed county, were reduced by 0.31 per 1000 and 9 per 100 000 respectively. Furthermore, the incidence rate due to stroke in the exposed county further slowed down, and the mortality rate due to stroke was reduced by 33 per 100,000 more than 30 years old population significantly. Conclusion: Following the implementation of the PEN project, the incidence rate due to MI and mortality rates due to MI and stroke decreased significantly. In addition, the incidence rate due to stroke further slowed down in the exposed county in comparison with the control county.